Health in the border area: what documents of Mercosur and Unasur reveal - Aikes, Solange; Rizzotto, Maria Lucia Frizon (Saúde e Sociedade, 2020)
This article analyzed the treatment given to the subject of health in the border area concerning Mercosur and Unasur. For such, a documentary research was performed in archives available in the electronic websites of these institutions with the keywords “health” and “border”. The data were analyzed using content analysis. In Mercosur, the subject is addressed in several meetings of the Subgroup on Health Work with the proposal of creating a Mercosur-Health consortium, which did not take effect. What it has advanced are proposals for the harmonization of general standards for health and epidemiological surveillance at borders. The recent creation of the Border Integration Working Subgroup 18 points to a greater concern with cross-translational processes. In Unasur, a more sympathetic view on the health issue in border area is observed, starting from the guarantee of the right to health to residents in these territories. Both institutions are shown to have played an important role in the development and integration process of the area. In contrast, social integration appears in an incipient manner. It is the responsibility of South American citizens, especially the border people, to recognize themselves as an integral part of these organizations and to fight for the recognition of the right to health as a fundamental human right.